Music information analysis and retrieval techniques - KOSTEK, Bożena; KANIA, Łukasz (Archives of Acoustics, 2008)
This paper presents the main issues related to music information retrieval (MIR) domain. MIR is a multi-discipline area. Within this domain, there exists a variety of approaches to musical instrument recognition, musical phrase classification, melody classification (e.g. query-by-humming systems), rhythm retrieval, high-level-based music retrieval such as looking for emotions in music or differences in expressiveness, music search based on listeners’ preferences, etc. The key-issue lies, however, in the parameterization of a musical event. In this paper some aspects related to MIR are shortly reviewed in the context of possible and current applications to this domain.